THE ROLE OF PREOPERATIVE PREPARATION AND POSTOPERATIVE REHABILITATION OF CHILDREN WITH HIP JOINT PATHOLOGIES - Alpysbaev Kh. Sh.; Dzhuraev A. M.; Tapilov E. A.; Kushabaev A. N. (Web of Journals Publishing, 2025)
The most common cause of disability in children with musculoskeletal disorders are dysplastic hip instability disorders, which include: hip dysplasia, congenital subluxation, and congenital and pathological hip dislocation.
Keywords: Hip joint, congenital hip dislocation, pathological hip dislocation, pathological hip dislocation, rehabilitation.